Culturally modified trees and forest structure at a Kawesqar ancient settlement at Rio Batchelor, western Patagonia - Ostlund, Lars; Zegers, Gabriel; Caceres Murrie, Benjamin; Fernandez, Macarena; Carracedo-Recasens, Robert; Josefsson, Torbjorn; Prieto, Alfredo; Roturier, Samuel (My University, 2020)
Indigenous land use occurring on temporal scales over centuries or millennia shapes forests in specific ways and influences the dynamics of forest ecosystems. It is challenging to study such land use, but analysis of "culturally modified trees" (CMTs) can give precise spatial and temporal information on past land use by indigenous people. The aim of this study was to increase our knowledge of indigenous use of land and resources in Nothofagus forests by identifying CMTs and analyzing the forest structure dynamics in an ancient Kawesqar settlement site in western Patagonia. Our results show that there are CMTs at Rio Batchelor and that the forest structure varies significantly within the site, indicating that Kawesqar people altered the forest by extracting various resources. We conclude that CMT studies have great potential in Nothofagus forests in southernmost America, but also face specific challenges due to environmental conditions and lack of corroborating historical information.
Keywords: culturally modified trees; bark peeling; forest history; indigenous land use; archaeology; patagonia; nothofagus